2016
DOI: 10.1186/s12889-016-3194-7
|View full text |Cite
|
Sign up to set email alerts
|

Partnership capacity for community health improvement plan implementation: findings from a social network analysis

Abstract: BackgroundMany health departments collaborate with community organizations on community health improvement processes. While a number of resources exist to plan and implement a community health improvement plan (CHIP), little empirical evidence exists on how to leverage and expand partnerships when implementing a CHIP. The purpose of this study was to identify characteristics of the network involved in implementing the CHIP in one large community. The aims of this analysis are to: 1) identify essential network … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(62 citation statements)
references
References 25 publications
5
56
1
Order By: Relevance
“…It has been used to examine a range of topics areas in health including community health coalitions [19], physician collaborations [20], relationships between tobacco control partners [21] and identifying the most powerful actors in public health policymaking [22]. A network consists of ‘ties’ which are patterns of association that link actors together; they can include informal linkages, based on communication and trust, as well as links based on the traditional institutionalized structures of co-ordination [23].…”
Section: Introductionmentioning
confidence: 99%
“…It has been used to examine a range of topics areas in health including community health coalitions [19], physician collaborations [20], relationships between tobacco control partners [21] and identifying the most powerful actors in public health policymaking [22]. A network consists of ‘ties’ which are patterns of association that link actors together; they can include informal linkages, based on communication and trust, as well as links based on the traditional institutionalized structures of co-ordination [23].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of references explored trust in social networks (n = 17), (30-35, 38-42, 49-54) while seven references explored trust in CBPR, (43)(44)(45)(46)(47)(48)55) and two explored both trust in social networks and CBPR. (36,37) Further individual study details and characteristics can be found in Additional File 3.…”
Section: Inclusion Of Sources Of Evidencementioning
confidence: 99%
“…Sustaining high levels of trust should become a key priority for coalition leaders moving forward." (37) Legend:ST: Sub-Theme, R(#): Outcome pertaining to Trust Similar to conceptualisation and operationalisation, R2 'relational' features of trust continued to be the most common parent theme for outcomes related to trust across studies. Comparatively, the second most prevalent parent theme was, R4 'features of social network analysis', indicating the reporting of more features of social network analysis connected with trust in some way (e.g., associated or indicating trust).…”
Section: Centralisationmentioning
confidence: 99%
“…Council effectiveness is often measured by member satisfaction, commitment to the coalition, and the quality of planning efforts 25 . While studies have also assessed trust, 26 inclusiveness, 27 and effectiveness 28 among members, there are to date no published studies using social network analysis for conducting a partnership gap analysis and associated partnership database. To highlight the utility of SNGA, this research presents a case study of the Southeastern Health Equity Council (SHEC).…”
Section: Introductionmentioning
confidence: 99%